2016
DOI: 10.1371/journal.pone.0141159
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Attenuates Splenomegaly in both Intrahepatic and Prehepatic Portal Hypertensive Rats by Blocking mTOR Signaling Pathway

Abstract: BackgroundSpleen enlargement is often detected in patients with liver cirrhosis, but the precise pathogenetic mechanisms behind the phenomenon have not been clearly elucidated. We investigated the pathogenetic mechanisms of splenomegaly in both portal hypertensive patients and rats, and tried to identify the possible therapy for this disease.MethodsSpleen samples were collected from portal hypertensive patients after splenectomy. Rat models of portal hypertension were induced by common bile duct ligation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…is may be the rapid activation of the bypassing loop that occurs in the rat with the infrarenal occlusion of the inferior caval vein (and thereby resolved Virchow) much like in the rats with ischemic/reperfusion colitis, duodenal venous congestion lesions, a perforated caecum, bile duct ligation-induced liver cirrhosis, and portal hypertension [48-50, 74, 81]. Accordingly, BPC 157 interacts with several molecular pathways [1,74,[82][83][84][85][86][87][88]. In particular, BPC 157 increased the expression and internalisation of VEGFR2 and the activation of the VEGFR2-Akt-eNOS signalling pathway without the need for other known ligands or shear stress [85].…”
Section: Discussionmentioning
confidence: 99%
“…is may be the rapid activation of the bypassing loop that occurs in the rat with the infrarenal occlusion of the inferior caval vein (and thereby resolved Virchow) much like in the rats with ischemic/reperfusion colitis, duodenal venous congestion lesions, a perforated caecum, bile duct ligation-induced liver cirrhosis, and portal hypertension [48-50, 74, 81]. Accordingly, BPC 157 interacts with several molecular pathways [1,74,[82][83][84][85][86][87][88]. In particular, BPC 157 increased the expression and internalisation of VEGFR2 and the activation of the VEGFR2-Akt-eNOS signalling pathway without the need for other known ligands or shear stress [85].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that angiogenesis and neovascularization play an important role in the development of splenomegaly and hypersplenism. For example, the mammalian target of rapamycin (mTOR) and Janus kinase-2 (JAK2/STAT3) signaling pathways, which are known regulators of angiogenesis, have been implicated in the development of portal hypertension and splenomegaly, and inhibition of these signaling pathways has been shown to reduce splenomegaly ( Mejias et al., 2010 ; Wang et al., 2015 ; Chen et al., 2016 ; Wang et al., 2016 ). Furthermore, it has been reported that elevated levels of vascular endothelial growth factor (VEGF), a critical regulator of angiogenesis and neovascularization, are associated with splenomegaly in patients with chronic myeloid leukemia ( Liu et al., 2005 ) and polycythemia vera ( Murphy et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also showed that splenomegaly was associated with splenic fibrosis in rats with PPVL 31 and that mTOR signaling promoted splenomegaly in these rats 31,32 . While splenic fibrosis was in agreement with our study, our results do not implicate genes related to mTOR signaling in splenomegaly.…”
Section: Discussionmentioning
confidence: 82%